PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Jessica Maharani; Murtanto Murtanto (STMIK Widuri Jakarta, 2024)
This research aims to determine the effect of liquidity, profitability and leverage on company value. The subject of thisresearch is the energy industry listed on the Indonesia Stock Exchange for the 2018-2021 period. The research designapplied is a causal study. The sampling technique uses a purposive sampling method. This method produces 58 companiesthat meet the criteria from a total of 80 companies during the 4 year observation period. The total sample includes 58companies. The data analysis method uses multiple linear regression analysis. The research results show that liquidityhas a positive effect on company value, while leverage and profitability have a positive effect on company value.